FAKTOR YANG MEMPENGARUHI WISATAWAN MEMBELI PRODUK HIJAU DI BALI BUDA UBUD, GIANYAR - Narayana, I Made Cahya; Kusuma Negara, I Made; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020), 2020)
A green product is one of the breakthrough innovations from the industry especially the tourism industry to achieve sustainable development. There are several reasons the green product is an eco- friendly product such as the use of organic ingredients and the production process. Hence, the objective of this research is to identify the factors affecting tourists’ willingness to pay for the green products at Bali Buda Ubud and what kind of factor that dominantly affects tourists’ willingness to pay Bali Buda Ubud green product. This research uses quantitative data technique analysis which processed by SPSS 23.0 for windows application. The sample is determined by a purposive sampling technique with 105 tourists who buy the green product of Bali Buda Ubud. The data collection techniques are observation, questionnaire, interview, literature review, and documentation. The data analysis techniques from this research are the validity test, reliability test, and factor analysis. The result of this research was that the factors which affect tourist’ willingness to pay green product of Bali Buda Ubud were company profit for environment conservation, green product good for health, the uniqueness of green product packaging, the pride of buying the green product, and knowledge about the green product. The dominant factor which affects tourist’ willingness to pay green product of Bali Buda Ubud was company profit for environment conservation which is seen from the biggest eigenvalue 8.373 and variance presentation 39.872%.